Peranan Dinas Pendidikan Dan Kebudayaan Kabupaten Takalar Dalam Meningkatkan Kualitas Guru Sekolah Dasar Di Kabupaten Takalar - Abdul Sahid; Ambo Masse (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
One of the factors that is very determining in efforts to improve the quality of human resources through education is the teaching staff or theachers, seeing this role, teachers must have agood and correct personality, be able to carry out their functions well, teachers must have certain conditions that have been metregulated in statutory regulations, in law number 14 of 2005 concerning teachers and lectures article 8. This research uses qualitative research with a population of 41 people and a sample of 20 people. Based on the research results. It shows that the efforts made are to provide opportunities for undergraduate teachers to take part in the PKB program to obtain a development certificate professionalism to then take certification. In creating this program ,the main targets were teachers in Takalar Regency,especially basic education teachers, with the aim of supporting efforts to accelerate the improvement of teacher quality so that they can have a positive impact in transmitting knowledge to students.